Pengaruh Modul Dan LKS Pada Materi Ciri-Ciri MakhlukHidup Terhadap Hasil Belajar Ipa Siswa Kelas VII SMPNegeri 1 Nguntoronadi Wonogiri Tahun Pelajaran2015/2016 - Alfi Rahmawati, Ria, Dra. Suparti, M.Si (2016)
Teaching materials is a set of means or instruments containing learning materials that aim to achieve a goal of learning expected. Teaching materials used in the study modules and worksheets. This study aims to determine the effect of the use of learning outcomes IPA modules and worksheets material characteristics of living things students of class VII SMP Negeri 1 Nguntoronadi in Wonogiri in the academic year 2015/2016. This research is quantitative. Data obtained using the method of observation and documentation methods to retrieve data science learning outcomes in class VII A study by using modules and class VII B using other teaching materials that worksheets characteristics of living things. The sampling technique random sampling technique. The results showed that learning by using the module has an average of 78.11, while learning with worksheets has an average of 70.31. Based on the results of this study concluded that learning to use the module has a greater influence dibandingakan learning by using worksheets for learning outcomes IPA material characteristics of living beings seventh grade students of SMP Negeri 1 Nguntoronadi in Wonogiri in the academic year 2015/2016